Is Cirrhosis a Contraindication to Laparoscopic Cholecystectomy?. Issue 1 (January 2015) - McGillicuddy, John W.; Villar, Juan JOSÉ E.; Rohan, Vinayak S.; Bazaz, Sapna; Taber, David J.; Pilch, Nicole A.; Baliga, Prabhakar K.; Chavin, Kenneth D.
Laparoscopic cholecystectomy is the gold standard treatment for the vast majority of patients with symptomatic cholelithiasis. Although cirrhotic patients are twice as likely to develop gallstones as compared with noncirrhotic patients, cirrhosis has historically been considered a relative, if not absolute, contraindication to laparoscopic cholecystectomy. More recently a number of authors have reported on the safety of laparoscopic cholecystectomy in cirrhotic patients. We reviewed our patients retrospectively and assessed the safety of laparoscopic cholecystectomy in cirrhotic patients as compared with noncirrhotics at a large liver transplant center. A retrospective longitudinal cohort study was conducted of all laparoscopic cholecystectomies performed by our surgical group between August 2002 and April 2011. Of 63 patients undergoing laparoscopic cholecystectomy, 32 (51%) were cirrhotic. Of the 30 for whom a Child score could be calculated, 11 (34%) were Child A, 14 (44%) were Child B, and five (16%) were Child C. The morbidity rate was 33 per cent and mortality rate was 2 per cent. Length of stay, conversion rates, 30-day readmission rates, and morbidity and mortality rates were not significantly different between the cirrhotic and noncirrhotic groups. There was a trend toward higher complication rates in Child C cirrhotics. Our results indicate that laparoscopic cholecystectomy can be performed with acceptable morbidity and mortality in carefully selected cirrhotic patients.